Community Participation in Maintenance of Environment Corporate Social Responsibility (CSR) PT. Pegadaian Region X Bandung - Riany Laila Nurwulan; Nina Kurniasih; HR. Sumardhani (Asian Social Work Journal, 2019)
This research has produced a model of three-pillar cooperation between government - private - community in the implementation of an activity for development. The government as a regulator issues development programs that aim to improve the welfare of the community, including development in the environmental field. Sustainable environment has an impact on comfort and public health. Not all of these programs are covered by the government due to government budget constraints. Therefore, in order for programs to be implemented it is necessary to have cooperation with the private sector, especially business entities in the form of limited liability companies, as stated in Law no. 40/2007 concerning Limited Liability Company article 74. In this case utilizing funds from a corporate social responsibility (CSR) program. Companies in the form of State-Owned Enterprises (BUMN) put them in the Partnership and Community Development Program (PKBL), including PT. Pegadaian. The statement of the problem in this study is that the need for community participation in environmental preservation. The study used qualitative methods with in-depth interview and observation data collection techniques. Data triangulation is used to complement data analysis. PT. Pegadaian Region X in the Pungkur Region realized the Environmental Development program in the environment in the Balonggede Sub-District of Regol Sub-District in 2016, namely planting ornamental plants in pots (red shoots) along the sidewalks of the Pungkur road and the Dalem Kaum road for approximately 80 units. After being handed over to the government of the Balonggede Village, its maintenance is the responsibility of the Balonggede Village by involving the surrounding community, especially the people who are close to or in contact with the object. The diversity of people's treatment of plants reflects different perceptions resulting in plants that are not in uniform growth conditions, some are well maintained and grow well, and some are in poor growth conditions. This shows a lack of ownership of public facilities, thus indicating a low level of community participation in environmental preservation, especially environmental facilities as asistance of PT. Pegadaian Region X.